Morphotype and Crust Effects on the Geochemistry of Globorotalia inflata. Issue 4 (8th April 2021) - Jonkers, Lukas; Gopalakrishnan, Akshat; Weßel, Lea; Chiessi, Cristiano M.; Groeneveld, Jeroen; Monien, Patrick; Lessa, Douglas; Morard, Raphaël
Abstract: Sedimentary specimens of the planktonic foraminifera Globorotalia inflata can provide information on subsurface conditions of past oceans. However, interpretation of their geochemical signal is complicated by possible effects of cryptic diversity and encrustation. Here we address these issues using plankton tow and sediment samples from the western South Atlantic, where two genotypes of G. inflata occur. To separate the genotypes, we analyzed shells from the extreme ends of the morphospace of G. inflata . The δ 18 O and δ 13 C of encrusted specimens from both morphotypes are indistinguishable. However, we do find a large influence of encrustation on δ 18 O and Mg/Ca. Whereas crust Mg/Ca ratios are at all locations lower than lamellar calcite, the crust effect on δ 18 O is less consistent in space. Plankton tows show that encrusted specimens occur at any depth and that even close to the surface crust Mg/Ca ratios are lower than in lamellar calcite. This is inconsistent with formation of the crust at lower temperature at greater depth. Instead we suggest that the difference between the crust and lamellar calcite Mg/Ca ratio is temperature‐independent and due to the presence of high Mg/Ca bands only in the lamellar calcite. The variable crust effect on δ 18 O is more difficult to explain, but the higher incidence of crust‐free specimens in warmer waters and the observation that a crust effect is clearest in the confluence zone, hint at the possibility that the difference reflects advective mixing of specimens from warmer and colder areas, rather than vertical migration. Key Points: No morphotype effect on the stable isotope composition of Globorotalia inflata Encrustation effect on geochemistry inconsistent with vertical migration Differences between crust and lamellar calcite may reflect banding or advection